Immediate hypersensitivity to chlorhexidine. (7th June 2017) - Vu, Mi; Rajgopal Bala, Harini; Cahill, Jennifer; Toholka, Ryan; Nixon, Rosemary
Abstract: Chlorhexidine is a widely used and effective antiseptic agent. Although skin contact is usually well tolerated, it may cause both immediate and delayed hypersensitivity reactions. We report a case of immediate hypersensitivity to chlorhexidine causing both skin and respiratory symptoms following occupational exposure to chlorhexidine in a health‐care worker.